ISOLATION, PURIFICATION, AND CHARACTERIZATION OF LIPASE FROM BACILLUS SP. FROM KITCHEN GREASE - R, Jaiganesh; Mk, Jaganathan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this work was to isolation, purification and characterization of solvent tolerant lipase from Bacillus sp. The objective of this work was to isolation, purification and characterization of solvent tolerant lipase from Bacillus sp. from kitchen grease for a variety of applications including organic synthetic reactions and preparation of enantiomerically pure pharmaceuticals. Methods: Lipase producing isolates were screened from kitchen grease on a selective medium rhodamine B olive oil agar, and tributyrin agar was used to screen the lipase and esterase producing an organism, respectively. The isolate identified using 16S rDNA sequencing method and enzyme activity was quantitatively assayed. Lipase production was characterized in different conditions. Results: The isolate showed highest lipase activity was which later was identified as Bacillus sp. using 16S rDNA sequencing method. The lipase was purified using ammonium sulfate precipitation. The isolate showed excellent tolerance to methanol, ethanol, acetonitrile, and moderate tolerance to butanol. The increased biomass concentration, maximum production, and activity were achieved at 37Â°C in 24 h incubation, then gradual reduction in production was observed. The maximum activity of lipase enzyme was obtained at pH between 6 and 9. Conclusion: The isolate produce solvent tolerance lipase enzyme and it can be a promising candidate of solvent tolerance lipase enzyme for variety of industrial applications.